Concept and optimization of SMA dampers to control the first three natural vibration modes in cable-stayed bridges - Ngoc Quy, Hoang; Duy, Nguyen Van; Nguyen, TruongGiang (Vietnam Journal of Science and Technology, 2025)
Cable-stayed bridges are often subjected to cable vibrations caused by wind, traffic, and other dynamic loads, which can significantly reduce their structural lifespan. To address this issue, our study proposes a two-floor damping design that leverages the superelasticity and superior energy dissipation capabilities of shape memory alloys (SMA). A simplified constitutive model was developed to simulate the superelastic behavior of SMA, optimizing critical parameters such as length, diameter, and installation position on cable-stayed bridges. Through simulations and dynamic response analysis, the SMA damper demonstrated exceptional effectiveness in dissipating energy across various vibration modes, significantly enhancing structural stability. Furthermore, this paper highlights the advantages of the two-floor SMA damper in mitigating cable vibrations under diverse oscillation modes and identifies an optimal set of parameters for practical installation, contributing to cost efficiency and extended bridge lifespan. A comparison with Tuned Mass Damper (TMD) results is also carried out to evaluate the damping efficiency of the SMA device.